1994
DOI: 10.1111/j.1574-6976.1994.tb00033.x
|View full text |Cite
|
Sign up to set email alerts
|

The biological degradation of cellulose

Abstract: Cellulolytic microorganisms play an important role in the biosphere by recycling cellulose, the most abundant carbohydrate produced by plants. Cellulose is a simple polymer, but it forms insoluble, crystalline microfibrils, which are highly resistant to enzymatic hydrolysis. All organisms known to degrade cellulose efficiently produce a battery of enzymes with different specificities, which act together in synergism. The study of cellulolytic enzymes at the molecular level has revealed some of the features tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
344
0
16

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,097 publications
(363 citation statements)
references
References 235 publications
3
344
0
16
Order By: Relevance
“…In addition to its function of binding other members of the cellulose complex to itself, it also binds to cellulose [10]. Its nucleotide sequence revealed a deduced protein size of 196,800 Da, a cellulose binding domain (CBD) [8] and nine enzyme receptor domains of about 150-166 amino acid residues each. The nine repeated sequences, called 'cohesins' by Bayer et al [5], are quite similar to each other, i.e., exhibiting between 60 and 100% identity, with six of the nine domains being at least 90% identical.…”
Section: Gram-positive Bacterial Anaerobesmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition to its function of binding other members of the cellulose complex to itself, it also binds to cellulose [10]. Its nucleotide sequence revealed a deduced protein size of 196,800 Da, a cellulose binding domain (CBD) [8] and nine enzyme receptor domains of about 150-166 amino acid residues each. The nine repeated sequences, called 'cohesins' by Bayer et al [5], are quite similar to each other, i.e., exhibiting between 60 and 100% identity, with six of the nine domains being at least 90% identical.…”
Section: Gram-positive Bacterial Anaerobesmentioning
confidence: 98%
“…Integration of cellulase production, sacchariWcation and fermentation into the microbial cell involves the use of thermophilic, anaerobic, ethanologenic bacteria such as Clostridium thermocellum [8,19,74]. C. thermocellum can convert both waste cellulose (i.e.…”
Section: Gram-positive Bacterial Anaerobesmentioning
confidence: 99%
“…Analysis of the molecular architecture of cellulases and xylanases has shown that many of these enzymes have a modular structure in which the functional domains are spatially separated by linker sequences [1][2][3]. These interdomain regions vary in size from six to over 300 amino acids, and generally consist of single amino acids [4] or of tandem repeats of dipeptides [5].…”
Section: Introductionmentioning
confidence: 99%
“…Microbial cellulases have become the important biocatalyst due to their complex nature and wide spread applications. The potential applications of cellulose are in food, animal feed, textile, fuel and chemical industries [1,2]. The major industrial applications of cellulases are in textile industry for biopolishing of fabrics and producing stonewashed look of denims, as well as household laundry detergents for improving fabric softness and brightness [3].…”
Section: Introductionmentioning
confidence: 99%